Protective effect of Clinopodium chinense (Benth.) O. Kuntze against abnormal uterine bleeding in female rats - Lili Li; Qi Huang; Xianchun Duan; Lan Han; Daiyin Peng (Elsevier, 2020)
Objectives: To investigated the metrorrhagia volume-reduction activity, anti-inflammatory activity and repair-promoting activity of Clinopodium chinense (Benth.) O. Kuntze. Methods: An abnormal uterine bleeding (AUB) model was induced via oral administration of mifepristone and misoprostol to pregnant rats, which were treated with the total extract of C. chinense (TEC). After 7 days, the metrorrhagia volume was measured, the levels of TXB2, 6-keto-PGF1α, IL-6 and TNF-α were measured by ELISA, the pathological changes and micro vessel density (MVD) of the endometrium were evaluated using HE and immunofluorescence staining, and the expression of VEGF, MMP-2/9 and TGF-β were assessed by Western blotting. Preliminary phytochemicals were screened and identified by UPLC-Q-TOF-MS. Results: Eleven compounds in C. chinense were identified via comparison to standard substances. The results of animal experiment showed TEC could reduce metrorrhagia volume, alleviate pathological injury and increase MVD to promote recovery of the endometrium; TEC could also increase the levels of TXB2 and the expression of VEGF, TGF-β, decrease the levels of IL-6, TNF-α and the expression of MMP-2/9. Conclusions: TEC showed beneficial effects on treating AUB by reducing metrorrhagia volume, inhibiting the inflammatory response and promoting the repair of the endometrium. Additionally, TEC also showed great haemostatic potential in AUB. Keywords: Biomolecules, C. chinense, Abnormal uterine bleeding, Metrorrhagia, UPLC-Q-TOF-MS